(untitled) (Praxis Educativa, 2023)
The purpose of the following article is to establish that the educational proposal that Gabriela Mistral put forward through various poems and prose should, from now on, be understood as praxis, since many of the proposals she made, when analyzed as a whole, allow us to propose a socio-historical Mistralian pedagogy, which is based on the rescue and respect for the cultural elements of the other and which has orality and mythology as central components of a Mistralian ethos. On the other hand, it is also observed that her educational praxis is framed within four dimensions: ethical, political, aesthetic, and pedagogical. The working methodology was based on the analysis of prose and poems, using as a selection criterion everything that was related to pedagogy, but also that the approach represented in his prose or poem was related to her educational experience.